2018
DOI: 10.1182/bloodadvances.2017014811
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, molecular, and immunological responses to pembrolizumab treatment of synchronous melanoma and acute myeloid leukemia

Abstract: Key Points Pembrolizumab treatment of melanoma and concomitant sAML resulted in a significant platelet response and clearance of IDH1 mutation. Pembrolizumab therapy and response was associated with an increased PD-L1 expression on acute myeloid leukemia blasts and T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…89,92,96 Nonetheless, single-agent therapy might display disease-modifying activity in selected patients, including elderly patients with AML. 97 Recent studies have also indicated the potential of targeting the innate immune checkpoint CD47-SIRPa in cancer, including hematologic cancers. 98,99 So far, blocking the interaction between the "don't-eat me" signal CD47 and the phagocyte inhibitory immunoreceptor SIRPa has shown low activity in a small AML/MDS cohort (1/10), but initial results from the combination therapy with 5-Aza are promising.…”
Section: Clinical Experience With Immune Interventionsmentioning
confidence: 99%
“…89,92,96 Nonetheless, single-agent therapy might display disease-modifying activity in selected patients, including elderly patients with AML. 97 Recent studies have also indicated the potential of targeting the innate immune checkpoint CD47-SIRPa in cancer, including hematologic cancers. 98,99 So far, blocking the interaction between the "don't-eat me" signal CD47 and the phagocyte inhibitory immunoreceptor SIRPa has shown low activity in a small AML/MDS cohort (1/10), but initial results from the combination therapy with 5-Aza are promising.…”
Section: Clinical Experience With Immune Interventionsmentioning
confidence: 99%
“…46 First-line pembrolizumab therapy, however, was shown to induce a clinical and molecular response in a patient with secondary AML receiving the drug for melanoma. 47 Similar to pembrolizumab, no responses were seen in advanced MDS patients treated with the PD-1 inhibitor nivolumab after HMA failure. 45 Interestingly, in MDS and secondary AML, PD-L1 expression levels are higher in hematopoietic cells than in those of healthy volunteers and resistance to the HMA azacitidine and decitabine is additionally associated with up-regulation of PD-1 and PD-L1 on leukemic cells, representing an immune evasion mechanism against HMA.…”
Section: Strategies For High-risk Mdsmentioning
confidence: 99%
“…Findings from small subgroups of responders ( n = 3) versus non-responders ( n = 3) documented an increased diversity of TCR Vβ repertoires in CD8 + T cells from responders. A recent case report documented disease-modifying activity of pembrolizumab in an AML patient with synchronous cutaneous melanoma [108]. It is presently unknown whether selecting tumors for PD-L1 expression is the best way to optimize PD-L1 blockade in hematological malignancies.…”
Section: Immune Checkpoint Blockade and Novel Immunotherapies For mentioning
confidence: 99%